The Growth of Red Mangrove (Rhizophora mucronata) in Nursery at Muara Village, Teluk Naga Subdistrict, Tangerang Regency PERTUMBUHAN BAKAU MERAH (Rhizophora mucronata) DI PERSEMAIAN MANGROVE DESA MUARA, KECAMATAN TELUK NAGA, KABUPATEN TANGERANG - Omo Rusdiana; Andi Sukendro; Ahmad Baiquni Rangkuni (Jurnal Silvikultur Tropika, 2015)
The success of mangrove rehabilitations are influenced by various factors which one of them is the availability of seedling stocks over time. The knowledge about growth process and development of plants which will be used as seedlings are several factors of success of nursery development. Red mangrove (Rhizophora mucronata) is one species of plants which grows in mangrove forest. The conservation of this species is very important because its habitat is at the central zone of mangrove formation and has high reproduction over time so it can be easier to do rehabilitation. The aim of this research is to get the information about R.mucronata growth and development to get better cultivation technique. The treatments were planting of propagule that had pieces of fruit and planting of propagul without pieces of fruit. Based on this research, the planting of propagule without pieces of fruit gave significant effect toward the heigth and length of red mangrove (R.mucronata) propagules development.Key words : growth, nursery, propagule, Rhizophora mucronata